Insecticide-treated bed net access and use among preschool children in Nouna District, Burkina Faso. Issue 3 (29th February 2020) - Sié, Ali; Bountogo, Mamadou; Ouattara, Mamadou; Zabre, Pascal; Bagagnan, Cheik; Zakane, Alphonse; Brogdon, Jessica; Lebas, Elodie; Lin, Ying; Godwin, William W; Bärnighausen, Till; Lietman, Thomas M; et al.
Abstract: Background: We evaluated universal insecticide-treated bed net access and use in children <5 y of age in a rural area of Burkina Faso. Methods: A door-to-door enumerative census was conducted in Nouna District, Burkina Faso in December 2018 through April 2019. The most recent mass bed net distribution campaign occurred in June 2016. Heads of households were interviewed about household bed net ownership and use by children <5 y of age. We evaluated the relationship between demographic and socio-economic factors and household universal bed net access and use by children. Results: In 23 610 households with at least one child <5 y of age, 71 329 bed nets were reported (94.5% insecticide-treated). One-third (35.2%) of households had universal access and two-thirds (67.0%) of children slept under an insecticide-treated net the previous night. Children in households with universal access more often slept under a net the previous night (adjusted odds ratio 4.81 [95% confidence interval 4.39–5.26]). Conclusions: Bed net coverage was substantially less than the 80% World Health Organization target for universal coverage in Nouna District. Insecticide-treated nets were used preferentially for children, but important gaps remain in consistent bed net use in this population. Structural and behavioural interventions are needed to close these gaps.